Evaluation of fetal arrhythmias from simultaneous pulsed wave Doppler in pulmonary artery and vein - Carvalho, Julene S (BMJ Group, 2007)
OBJECTIVE: To evaluate the clinical application of simultaneous recordings of pulsed wave Doppler (PWD) signals in pulmonary artery and vein as alternative sampling site for assessment of arrhythmias in the fetus. DESIGN: Prospective, cross‐sectional study. SETTING: Tertiary referral centre for fetal cardiology. PATIENTS AND METHODS: From July 1999 to July 2005 PWD was used in pulmonary vessels to assess fetal arrhythmias at 15–40 weeks' gestation. Sample volume placement in the peripheral lung vessels was guided by colour flow mapping on a four‐chamber section of the fetal heart. Atrial and ventricular systoles were identified from the pulmonary venous and arterial signals respectively. M‐mode recordings were used for comparison. OUTCOME MEASURES: Diagnosis of fetal arrhythmias. RESULTS: Of 129 cases, 15 had supraventricular tachycardia, 12 with 1:1 atrioventricular conduction and 3 with atrial flutter and 2:1 block. There were 96 cases of atrial and 7 of ventricular premature beats, 2 of sinus bradycardia, 8 of variable degree heart block and 1 of ventricular tachycardia. PWD was diagnostic in 119 cases. PWD was better than M mode for diagnosis of premature beats and added information about mechanisms of tachycardia. Both methods facilitated interpretation of all arrhythmia patterns, although PWD was of less practical value in cases of complete heart block. CONCLUSION: Simultaneous PWD recording of pulmonary vessels in the fetus allows accurate diagnosis of arrhythmias. It is easily obtained with standard ultrasound equipment and adds to the armamentarium of diagnostic techniques for assessment of rhythm abnormalities prenatally.